Strata + Hadoop World 2015 : complete video compilation (O'Reilly Media, 2015)
"Whether you want to build a company that will prosper well into the future, or simply do your job better, you'll want to dive into this complete video compilation of Strata + Hadoop World 2015 in New York, presented by O'Reilly and Cloudera. You'll have every keynote, tutorial, and workshop from big data's most influential business decision makers, strategists, architects, developers, and analysts right at your fingertips. Download these videos or stream them through our HD player, and get the practical data case studies, proven best practices, new analytic approaches, and exceptional technical skills you need to be successful with data."--Resource description page.